Liver transplantation for unresectable colorectal liver metastases: A systematic review. Issue 3 (17th May 2017) - Moris, Dimitrios; Tsilimigras, Diamantis I.; Chakedis, Jeffery; Beal, Eliza W.; Felekouras, Evangelos; Vernadakis, Spiridon; Schizas, Dimitrios; Fung, John J.; Pawlik, Timothy M.
Abstract : The use of liver transplantation (LT) for liver metastases attempted in the early 1990's was associated with poor perioperative outcomes and unacceptably low overall survival. Recently, there has been renewed interest in LT as a treatment option for colorectal liver metastases (CLM) in countries where organ supply is high. To date, no meticulous analysis about the efficacy, safety and outcomes of LT in CLM patients has been published. We present the first systematic review on the subject.